PENANAMAN NILAI-NILAI SHODAQOH MELALUI PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 BOYOLANGU TULUNGAGUNG - Nurhadi, Nurhadi (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2016)
AbstractThe purpose of this study is to find out how the implementation of planting values of faith, sincerity value and social value to learners through Islamic Education. Results of the study are: planting is done with the values of faith bilhal (behavior), and practical. The development of value investment is able to enter into self-learners, the proof is diligent student worship and bershodaqoh; Planting the value of sincerity is done by applying or familiarize the learners to bershodaqoh; Social value Planting is done by holding social events that the students are trained to look at the condition of the society and the individual. In addition, so that students are able to apply in the midst of society.